Immobilization of Quantum Dots on Fluorescent Graphene Oxide for Ratiometric Fluorescence Detection of Copper Ions. Issue 20 (11th July 2017) - Zhu, Houjuan; Xu, Hongda; Yu, Huan; Zhang, Kui; Hayat, Tasawar; Alsaedi, Ahmed; Wang, Suhua
Abstract: Graphene oxide with stable fluorescence has been synthesized and utilized to support and functionalize quantum dots for dual‐emissive nanostructure construction. The two emissions from graphene oxide and quantum dots are differently and independently responsive to copper ions (Cu 2+ ). The blue fluorescence of graphene oxide is very stable against Cu 2+, whereas the red fluorescence from quantum dots can be selectively quenched, inducing the composite fluorescent color change from bright red to blue. Such a novel nanocomposite can be applied for selective and sensitive determination of Cu 2+ . For practical application, the graphene based nanohybrid has been immobilized in polymer film to fabricate fluorescence test strip for Cu 2+ . A visual detection limit of 0.1 μM for the film test strip has been estimated and shows the potential application for on‐site visual determination of Cu 2+ with no need for elaborate equipment. Abstract : Copper ion selectively reacts to red fluorescent dithiothreitol‐functionalized quantum dots supported on blue fluorescent grapheme oxide sheet (QDs‐FGO) and leads to a ratiometric fluorescence color change. A paper indicator based on the QDs‐FGO nanocomposite is built for on‐site visible determination of copper ions with a limit detection of 0.1 μM.